IN VIVO FUNCTIONAL EVALUATION OF STIM1 AS A CANDIDATE GENE RESPONSIBLE FOR EXAGGERATED SYMPATHETIC RESPONSE TO STRESSES IN SHRSP: ESTABLISHMENT OF STIM1 KNOCK-IN SHRSP. (June 2018) - Ohara, H.; Batbayar, O.; Ngarashi, D.; Kunihiro, Y.; Kaneko, T.; Mashimo, T.; Nabika, T.
Abstract : Objective: Increased activity of sympathetic nervous system is a possible mechanism related to development of severe hypertension in the stroke-prone spontaneously hypertensive rat (SHRSP). In the previous studies, we identified stromal interaction molecule 1 (Stim1) as a promising candidate gene responsible for the exaggerated sympathetic response to stresses in SHRSP. A nonsense mutation (p.Arg640X) was found in its coding sequence, resulting in expression of a truncated form of STIM1 and a decrease in store-operated calcium entry (SOCE) mediated by Orai1 or TRPC. In the present study, we generated Stim1 knock-in SHRSP (SHRSP-Stim1em1Kyo), in which the nonsense mutation was rescued by CRISPR/Cas9 system, to investigate whether Stim1 is a causative gene for hypertensive phenotype of SHRSP. Design and method: SHRSP-Stim1em1Kyo was established by microinjection of gRNA, Cas9 mRNA and ssODN with target site sequence of rat Stim1 to embryos from SHRSP/Izm. SHRSP/Izm was used as control strain throughout the experiments. Cerebral astrocytes were cultured from newborn rats (1–3 days after birth) by a shaking method. The SOCE activity in the cultured astrocytes were evaluated by calcium imaging using Fluo-8 AM. Blood pressure (BP) was measured by tail-cuff method. Urine was corrected from a rat kept in a metabolic cage at room temperature/4°C for 6 h and urinary norepinephrine excretion (u-NE) was analyzed by HPLC in SRL (Tokyo, Japan). Changes in uNE with or without the cold stress was calculated as an indicator of sympathetic activity to the stress. Results: Establishment of homozygous SHRSP-Stim1em1Kyo was confirmed by DNA sequencing and western blotting which showed expression of wild-type STIM1 protein in brainstem. The expression level in SHRSP-Stim1em1Kyo was significantly greater than that in SHRSP/Izm. Increased SOCE activity was found in astrocytes from SHRSP-Stim1em1Kyo compared with that from SHRSP/Izm. No significant differences were found in both SBP at 12, 16 and 20 weeks of age and changes in u-NE between the two strains. Conclusions: Improvement of STIM1 function in SHRSP/Izm may not affect its sympathetic activity to the cold stress.